Penyusunan Bibliografi Beranotasi Seri Bacaan Sastra Koleksi Perpustakaan Jurusan Bahasa dan Sastra Indonesia dan Daerah Universitas Negeri Padang - Afdal, Afdal; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper aims to describe the preparation of an annotated bibliography series of children's literature reading library collections Department of Language and Literature Indonesia Region Padang State University.The method used is descriptive method. Data collected by observation or observation. Observations were made directly browse the collection of literature reading series at the Library of the Department of English Literature Indonesia and the region. Once obtained, selanjutkan to identify the parts that will be created for the annotated bibliography. The results obtained in the direct observation, the number of collections of literary reading series at the Library of the Department of Language and Literature Indonesia Region Padang State University has 590 readings series, but this paper is only 10% percent are 59 collections of literary reading series.Based on the discussion can be concluded the stage of making annotated bibliography of literature reading series are as follows. First, the determination of children's literature reading series title. Second, the collection of library material by recording the bibliographic data such as the author's name, title of a series of literary readings, Impresum, as well as other information such as the number to call. Third, the selection of library materials be selected on the entire collection of literary reading series by splitting a series of readings alphabetically. Fourth, grouping or classification annotated bibliography of literature reading series are grouped by classification fundamentals that classify library materials based on the content or subject matter. Fifth, the keyword generation. Sixth, penyusanan index. Seventh, typing the manuscript biliografi contain elements such as writing an author's name, title of a series of readings, Impresum and other information required in making an annotated bibliography.Keyword: art, bibliography, reading.